Cognitive impairment does not impact sacral neuromodulation implant rates for overactive bladder. Issue 3 (26th January 2023) - Zillioux, Jacqueline; Lewis, Kevin C.; Hettel, Daniel; Goldman, Howard B.; Vasavada, Sandip P.; Gill, Bradley C.
Abstract: Objective: To evaluate the impact of cognitive impairment (CI) diagnoses on sacral neuromodulation (SNM) outcomes in older patients. Materials and Methods: We completed a retrospective review of all patients aged ≥55 years who underwent test‐phase SNM (peripheral nerve evaluation (PNE) or stage 1) for overactive bladder (OAB) between 2014 and 2021 within a large multi‐regional health system. Patient demographics, relevant comorbidities, CI diagnoses (dementia or mild CI), and SNM procedures were recorded. Logistic regression modeling was performed to evaluate the impact of CI on SNM implantation rates. Results: Five‐hundred and ten patients underwent SNM test phase (161 PNE, 349 Stage 1) during the study period. The mean age was 71.0(8.5) years, and most (80.6%) were female. Overall, 52(10.1%) patients had a CI diagnosis at the time of SNM, and 30 (5.8%) were diagnosed at a median of 18.5 [9.25, 39.5] months after SNM. Patients with CI diagnoses were older, with more comorbidities, and were more likely to undergo PNE. Univariable comparison found no difference in implantation rate based on pre‐SNM CI (85.4% vs. 76.9%, p = 0.16). Multivariable analysis identified PNE (OR 0.43, 95% CI 0.26–0.71), age (OR 0.96, 95%CI 0.93‐0.98), and prior beta‐3 agonist use (OR 0.60, 95% CI 0.37‐0.99) but not CI or dementia as independent negative predictors of implantation. Implanted patients had a median follow‐up of 25 [12.0, 55.0] months. Explant and revision rates did not differ according to CI. Conclusion: Patients with OAB and CI diagnoses proceed to SNM implant at rates similar to patients without CI diagnoses. A diagnosis of CI should not necessarily exclude patients from SNM therapy for refractory OAB.